Enhancing Automotive Brand Value: Achieving Zero-Defect Software Product Development in Vehicles - Arumuga Nainar, Sudalai Veerapandian (Digital Repository of Theses, 2025)
This study investigates the impact of achieving zero-defective software on the brand value of automotive companies, focusing on how software quality influences consumer perceptions, customer loyalty, and competitive advantage. Using qualitative methods, in-depth interviews were conducted with 112 participants from diverse roles, including software engineers, quality assurance experts, brand managers, and customers, to gain comprehensive insights into these dynamics. The thematic analysis revealed that high-quality, defect-free software significantly enhances brand value by fostering consumer trust, improving user experiences, and positioning brands as technologically advanced and reliable. Conversely, software failures, such as bugs or compatibility issues, were found to severely damage brand perception and customer loyalty. Key challenges in achieving zero-defective software included managing the complexity of integrating multiple software components, ensuring comprehensive testing under real-world conditions, and balancing innovation with reliability. The study's practical implications highlight the importance of adopting Agile methodologies, rigorous testing frameworks, and continuous integration practices to reduce defects and enhance software reliability. These findings provide actionable strategies for automotive companies aiming to improve software quality, strengthen brand loyalty, and maintain a competitive edge in an increasingly digital automotive market. Keywords: Zero-defective software, automotive industry, brand value, customer loyalty, software quality